Mathematical analysis of maximum power generated by photovoltaic systems and fitting curves for standard test conditions - Gabriel Filho, Luís R. A. [UNESP]; Viais Neto, Daniel Dos S.; Cremasco, Camila P. [UNESP]; Seraphim, Odivaldo J.; Caneppele, Fernando De L. (FapUNIFESP (SciELO), 2012)
The rural electrification is characterized by geographical dispersion of the population, low consumption, high investment by consumers and high cost. Moreover, solar radiation constitutes an inexhaustible source of energy and in its conversion into electricity photovoltaic panels are used. In this study, equations were adjusted to field conditions presented by the manufacturer for current and power of small photovoltaic systems. The mathematical analysis was performed on the photovoltaic rural system I-100 from ISOFOTON, with power 300 Wp, located at the Experimental Farm Lageado of FCA/UNESP. For the development of such equations, the circuitry of photovoltaic cells has been studied to apply iterative numerical methods for the determination of electrical parameters and possible errors in the appropriate equations in the literature to reality. Therefore, a simulation of a photovoltaic panel was proposed through mathematical equations that were adjusted according to the data of local radiation. The results have presented equations that provide real answers to the user and may assist in the design of these systems, once calculated that the maximum power limit ensures a supply of energy generated. This real sizing helps establishing the possible applications of solar energy to the rural producer and informing the real possibilities of generating electricity from the sun.
Keywords: Numerical methods; Photovoltaic cells; Rural electrification